Study of Financial Literacy Among College Students in a Public University, Borneo Tarakan Indonesia - Juliana, Ahmad (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2017)
This paper aims to examine gender differences in financial literacy among college students in Borneo Tarakan University. We use Multistage Random Sampling method. The research recruits 325 college student form Department of Management, Faculty Economic. The findings indicate gender differences function in different aspects of financial literacy. Female students are better literate than male student. The findings confirm basic concept of financial literacy in Compound of Interest and Inflation. In terms of level differrence the level 2 better literate than level 1 and 3, this confirm to all basic concept literacy. As for age differences, college students of 19-20 years old are better literate. Meanwhile, the results of college student with working experience are better than student without working experience in Compound of Interest and Inflation concept. However, we got different results on stock risk concept, college student without working experience are better literate than college students with working experience.